2009
DOI: 10.1016/j.jacc.2009.04.051
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Strength of Evidence for Heart Failure Disease-Management Programs?

Abstract: Heart failure (HF) disease-management programs are increasingly common. However, some large and recent trials of programs have not reported positive findings. There have also been parallel recent advances in reporting standards and theory around complex nonpharmacological interventions. These developments compel reconsideration in this Viewpoint of how research into HF-management programs should be evaluated, the quality, specificity, and usefulness of this evidence, and the recommendations for future research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 54 publications
0
51
0
2
Order By: Relevance
“…Although samples used in other studies from the USA (8,25) and Spain (20) showed similar characteristics, most of the samples have considerably higher socio-economic and educational levels. In the future, we propose including this kind of population in a new study in order to improve our knowledge about that population's health.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although samples used in other studies from the USA (8,25) and Spain (20) showed similar characteristics, most of the samples have considerably higher socio-economic and educational levels. In the future, we propose including this kind of population in a new study in order to improve our knowledge about that population's health.…”
Section: Resultsmentioning
confidence: 80%
“…Given the importance of HRQOL to patients, the adaptation of disease management interventions to support effective self-care of HF in Brazil is a priority (16)(17)24) . Programs to support self-care should include both patients and partners and examine ways to ensure that the many facets of these interventions are accessible and beneficial to patients with very low socioeconomic and educational levels (9,(24)(25) .…”
Section: Resultsmentioning
confidence: 99%
“…Meta-theories such as positivism struggle to subsume such demonstrable inconsistencies-and usually attribute the wide variability in findings to issues around method-notably intervention fidelity, study differences in populations, outcomes, and comparison groups (Clark et al, 2009). Seldom is ontology invoked.…”
Section: Role Of Cr In Shaping Our Research Around Complex Hfdmismentioning
confidence: 99%
“…From these earlier studies, major factors that may affect living with CHF and self-care include lack of knowledge, inadequate communication with providers, loss of social support, multiple co-morbidities, medication issues, physical limitations, loss of control, loss of meaningful activities, fear of getting worse, daily uncertainty, helplessness and the emotional impact of illness [13,14].…”
Section: Discussionmentioning
confidence: 99%